Pharmacological modulation of Sigma-1 receptor ameliorates pathological neuroinflammation in rats with diabetic neuropathic pain via the AKT/GSK-3β/NF-κB pathway - Yuyu An; Shanshan Cao; Leilei Shi; Yuhan Zhang; Xin Wang; Shiyu Yuan; Yongheng Shi; Bin Wang; Jiping Liu; Chao-jun Han (Brain Research Bulletin)
Diabetic neuropathic pain (DNP) is a common complication of diabetes mellitus (DM) and is characterized by spontaneous pain and neuroinflammation. The Sigma-1 receptor (Sig-1R) has been proposed as a target for analgesic development. It is an important receptor with anti-inflammatory properties and has been found to regulate DNP. However, it is not known whether Sig-1R can ameliorate pathological neuroinflammation in DNP. The present study used a rat model of DNP and a highly selective agonist of Sig-1R to assess the effects of the protein on neuropathic pain in rats with type 2 diabetes mellitus. The rats were divided into Control, Model, Sig-1R agonist PRE-084 (0.3, 0.6, 1 mg/kg), and metformin (Met, 20 mg/kg) groups, with seven rats per group, and their body weight, fasting blood glucose, mechanical withdrawal threshold and thermal withdrawal latency were tested weekly for two weeks. After treatment with PRE-084, the pain thresholds in the DNP rats were significantly improved, together with pathological changes in the dorsal root ganglion, reductions in the serum levels of TNF-α, IL-1β, IL-6, MOD, and prostaglandin E2 (PGE2), and the activity of superoxide dismutase was increased. The mRNA levels of TNF-α, IL-1β, and cyclooxygenase 2 (COX-2) were reduced. Pharmacological inhibition of Sig-1R with BD1047 (10 μM) abolished Sig-1R-mediated activation of lipopolysaccharide-treated BV-2 microglial cells. It was also found that PRE-084 increased phosphorylation of serine/threonine protein kinase B (AKT) and glycogen synthase kinase 3β (GSK-3β) at Ser9, inhibiting nuclear factor kappa B (NF-κB)-mediated neuroinflammation in the dorsal root ganglion, thus reducing DNP. The findings suggest that the effect of Sig-1R agonist PRE-084 on DNP may reduce the level of inflammation through the up-regulation of AKT/GSK-3β and down-regulation of the NF-κB signaling, thereby contributing to the treatment of the disease.